Symbolic centrality of the central temple of the Igreja Universal do Reino de Deus in Fortaleza: Symbolic centrality of the central temple of the Igreja Universal do Reino de Deus in Fortaleza (Élisée - Revista de Geografia da UEG, 2021)
This text analyzes the religious manifestation that is expressed in the city from the study of the Igreja Universal do Reino de Deus (IURD) in Fortaleza, Ceará. It is the way in which the central temple of the IURD symbolically expresses a centrality for the faithful of this religious institution. Based on a cultural approach in geography, religion is a focus for socio-spatial understanding regarding the manifestation of the sacred in the center of Fortaleza. The goal is to understand the symbolic centrality of the Igreja Universal do Reino de Deus in Fortaleza. Part is a mapping of the temples in the city, and field visits, heed to the considerations of the faithful regarding the symbolic elements that make them prefer the cathedral over the temples in the neighborhood. Therefore, it is verified that the state seat of the IURD exercises a symbolic centrality, since it composes a symbolic spatial form that exerts power and influence in the urban scenario for its regulars.Keywords: Centrality; Symbol; Igreja Universal do Reino de Deus
Keywords: Centrality; Symbol; Igreja Universal do Reino de Deus